Action Research in Translation Studies - Josélia Neves; Ana Cravo (JoSTrans: The Journal of Specialised Translation)
In this paper we aim to address the meaning of Action Research (AR), its use and the possibility of its application to the field of Translation Studies (TS). Research into new areas, such as Audiovisual Translation, often leads to the questioning of common practices and theories, wishing to find those that best respond to the issues that derive from complex textual types and from the myriad of constraints that might be involved in those translation actions. It is in such a context, that we first questioned the possibility of using Action Reseach in Translation Studies (ARTS).